Design and synthesis of biodegradable grafted cationic polycarbonates as broad spectrum antimicrobial agents. Issue 8 (27th November 2015) - Ong, Zhan Yuin; Coady, Daniel J.; Tan, Jeremy P. K.; Li, Yan; Chan, Julian M. W.; Yang, Yi Yan; Hedrick, James L.
Abstract : Several biodegradable grafted cationic polycarbonates prepared via metal‐free organocatalytic ring‐opening polymerization are investigated for their antimicrobial activity, mechanism of action, and biocompatibility.